Electric vehicles and smart traffic systems as urban emission solutions: an analysis of jakarta within the SDG framework - Dachi, Ichsan Azis; Sinambela, Rismen (Institute of Computer Science (IOCS), 2026)
Jakarta, as one of the largest metropolitan cities, faces significant environmental pressures due to urbanization and high vehicle volumes. This paper examines technological innovations in sustainable transportation in Jakarta, aiming to fundamentally reduce carbon emissions and improve energy efficiency. Technologies such as electric vehicles (EVs), alternative fuels, and intelligent traffic management systems (ITS) offer potential solutions to address the city's chronic air pollution and congestion issues. However, the implementation of these technologies faces significant challenges such as limited charging infrastructure, high initial implementation costs, and the complexity of integrating with existing public transportation systems. An in-depth analysis was conducted to compare the existing situation with the targets of Sustainable Development Goals (SDGs) 7 (Clean Energy) and 11 (Sustainable Cities), identifying significant gaps in achieving these targets, particularly in the use of renewable energy and improving air quality. The study concludes that while these technologies offer a promising pathway, successful adoption relies heavily on strong policy commitments, strategic investments, and collaboration among transportation institutions to achieve truly sustainable urban mobility